THE PANEL FOR BOTH DRAINAGE AND WATER STORAGE, AND GREEN ROOF SYSTEM USING THE SAME - KWON, HYUK JUN (2006)
A drainage-cum-water storage panel and a green roof system using the drainage-cum-water storage panel are provided to reduce the load applied on a building and a period of construction by using a drainage-cum-water storage panel having the function of drainage, water storage and root barrier. A drainage-cum-water storage panel comprises a drainage passage(410) provided with through holes(440) to move moisture up to the panel to be supplied to a vegetation layer and a soil layer, a water storage unit(420) connected with the drainage passage by a connecting groove to keep the stored water not to be drained off through the drainage passage, a connecting groove(430) connecting the drainage passage and the water storage unit, and a joint end(450) composed of an L-shaped primary joint end and a U-shaped secondary joint end and coupling unit panels tightly with a joint pin. A green roof system using the panel for drainage and water storage comprises a roof floor, a waterproof layer formed on the roof floor to cut off the permeation of moisture to a building, a waterproof protective layer installed on the waterproof layer to protect the waterproof layer against physical damage, a drainage-cum-water storage panel installed on the waterproof protective layer to the function of drainage and water storage, a water storage member composed of gravel and filled in the water storage unit of the drainage-cum-water storage panel to supply water to a soil layer easily, a water permeable layer formed on the drainage-cum-water storage panel and composed of a water permeable sheet and a water permeable mat to absorb the stored water in the drainage-cum-water storage panel and to supply to a soil layer, a soil layer formed on the water permeable layer and made of organic soils to promote the growth of planes, and a vegetation layer formed on the soil layer.